Investigation of Production Process and GC-MS Analysis of Chemical Constituents of Three Traditional Medicines Sumbawa Oils - Hadi, Surya; Yunita, Yunita; Sutrisna, Ziki; Agustina, Marlina; Fadila Arlina, Baiq; Rizkya Satriani, Andhina; Hizmi, Surayyal (Chemistry Department, The University of Brawijaya, 2018)
The aims of this research are to study the production process and the chemical composition of three traditional Sumbawa oils from Benete Village (BT), Batu Dulang Village (BD), and Hutan Sumbawa (HS). A survey was conducted to learn the production process and the chemical composition of the Sumbawa oils was determined by fractionation method using three solvents with different polarity (methanol, dichloromethane (DCM) and n-hexane), followed by GC-MS analysis of each extract. In general, the three Sumbawa Oils were traditionally produced by mixing various species of medical plants into the coconut oil through heating process. Based on GC-MS analysis, the constituents of the Sumbawa oils are mainly fatty acid, fatty acid ester, monoterpene and sesquiterpene. Three major identical compounds were identified in all three products with different percentages of abundance namely Octadecanoic acid/stearic acid, Hexadecanoic acid/palmitic acid, and methyl palmitate. Furthermore, there were other major compounds such as Linoleic acid, Lycopersene, and Dodecanoic acid/lauric acid. The non-natural product compounds found in Sumbawa oil extracts and the biological activities of major compounds are discussed in this article.